Sum

Solve the following systems of equations by eliminating ‘y’ (by substitution) :

7x + 11y – 3 = 0

8x + y – 15 = 0

Advertisement Remove all ads

#### Solution

We have,

7x + 11y – 3 = 0 ….(1)

8x + y – 15 = 0 …..(2)

From equation (1), we get;

7x + 11y = 3

`⇒ y = \frac{3-7x}{11}`

Substituting the value of ‘y’ in equation (2), we get

`⇒ 8x + \frac{3-7x}{11} = 15`

⇒ 88x + 3 – 7x = 165

⇒ 81x = 162

⇒ x = 2

Now, substituting, x = 2 in the equation (2), we get

8 × 2 + y = 15

⇒ y = – 1

Hence, x = 2, y = – 1

Concept: Algebraic Methods of Solving a Pair of Linear Equations - Substitution Method

Is there an error in this question or solution?

Advertisement Remove all ads